Pushback: The limits of power in Erdogan's Turkey - Jakob Lindgaard (Danish Institute for International Studies (DIIS), 2024)
There is a widespread perception these years that strongmen around the world are winning, posing new geopolitical challenges and threats to the Western liberal order and security architecture. This DIIS Report takes a closer look at one of these strongmen, Turkey's Recep Tayyip Erdogan. The picture it paints, however, is not one of confidence and strength. Rather, the statements and actions of Erdogan and Turkey increasingly seem to be born of the frustration that increasing pushback against both him and his Turkey elicits. The report unfolds how and why this is. [...]
Keywords: 300; Turkey; Erdogan; Turkish nationalism; geopolitics; NATO; the West